Pettit, Non-domination and Agency: A Taylorian Assessment - McLaughlin, Adam Bernard (Université d'Ottawa / University of Ottawa, 2016)
Philip Pettit claims his neorepublican theory of freedom as non-domination is preferable to the liberal ideal of non-interference, and he is right. But the reasons why he is right run deeper than is apparent if we attend solely to his arguments defending non-domination in negative terms. In fact, embedded in the three benefits that Pettit claims non-domination can offer (which non-interference cannot) lie significant resonances with a positive idea of freedom concerned with a person’s sense of agency. We find such an idea in Charles Taylor, where freedom as self-realization is intricately linked with his “significance view” of human agency. By adopting this Taylorian lens and assessing Pettit’s non-domination, I show that non-domination does have much to offer those of us who think of freedom primarily in positive terms and, more generally, to all those of us who believe that freedom and agency are inextricably linked and must be treated as such.
Keywords: Philip Pettit; Charles Taylor; Republicanism; Non-domination; Agency; Positive Liberty; Negative Liberty